E‐referrals and teledermatoscopy grading for melanoma: a successful model of care. (16th February 2020) - Sunderland, Michael; Teague, Rebecca; Gale, Katherine; Rademaker, Marius; Oakley, Amanda; Martin, Richard C. W.
Abstract: Background/Objectives: An e‐referral system was developed at a tertiary care hospital in Auckland, New Zealand in 2014 for suspected cutaneous malignancy. E‐referrals include patient information, a description of the lesion(s), biopsy results and/or attached photograph(s). Experienced surgical oncologists prioritised the referrals and selected a management option or referred them for a teledermatoscopy opinion. Our aim was to review the efficacy of e‐referrals for improving diagnostic accuracy for melanoma. Methods: Referrals received in 2016 including images and categorisation as confirmed, likely or suspected melanoma by the triage specialist were evaluated. Concordance of the pathological diagnosis with the triage diagnosis and teledermatoscopy diagnosis was determined for each referral. Results: 809 of 3470 e‐referrals for skin cancer were categorised as confirmed, likely or suspected melanoma. 230 (28.4%) of these included a referral histopathology confirming melanoma/melanoma in situ. Of the remaining 579 referrals, 315 were sent for urgent diagnostic excision and 264 were referred for teledermatoscopy. 120 of the 315 sent for urgent excision were confirmed as melanoma (53) or melanoma in situ (67) on histopathology: a positive predictive value (PPV) of 38.1% and number needed to excise (NNE) of 2.6. Less than 10% of referrals triaged for teledermatoscopy were confirmed as melanoma (24/264). Almost half of all referrals (374/809, 45.6%) included melanoma/melanoma in situ. The melanoma: melanoma in situ ratio was 1: 1.18. Conclusions: The e‐referral and teledermatoscopy service for suspected melanoma has proven fewer unnecessary excisions of benign lesions than previously reported.